Clint Eastwood : Interviews, Revised and Updated - Eastwood, Clint, 1930- (Book collections on Project MUSE., 2013)
Clint Eastwood (b. 1930) is the only popular American dramatic star to have shaped his own career almost entirely through films of his own producing, frequently under his own direction; no other dramatic star has directed himself so often. He is also one of the most prolific active directors, with thirty-three features to his credit since 1971. As a star, he is often recalled primarily for two early roles--the ""Man with No Name"" of three European-made Westerns, and the uncompromising cop ""Dirty"" Harry Callahan. But on his own as a director, Eastwood has steered a remarkable course. A.